PRECIPITATION EVENT ANALYSIS USING IMAGE PROCESSING BASED ON THE RAINFALL DETECTION RADAR (RDR) OBSERVATION ON MARCH 9 2014 DURING LANDSLIDE EVENT IN WEST JAVA - Nugroho, Ginaldi Ari; Satyawardhana, Haries; Yulihastin, Erma; Satiadi, Didi; Halimurrahman, Halimurrahman (Teknologi Indonesia, 2016)
A Rainfall Detection Radar (RDR) is a simple weather radar based on marine radar that able is to detect the rainfall within 40 km of range located in Bandung. This system is able to conduct continuous operation, with temporal resolution of 3 minutes with data analysis using an image processing method, to analyze the observation data on March 9, 2014 during the landslide event. The landslides are located 24.6 km southwest from the RDR site. According to observation data, there are 2 large rainfall areas distribution that appear near the landslide location. The second rainfall area is estimated to have initiated the landslide. This second area has two detected object. Object A showed first with maximum size of + 6.47 km 2 . From the image processing point of view, the object A contributesto the size area of object B. Object B is the second object detected soon after object A appears. Object B has three peaks of its estimated size area with the highest size of + 19.4 km 2 occuring in 16.14 LT, and will move towards the southeast affected by local wind leaving the landslide location in 16.37 LT. RDR mean rainfall intensity in radius of 1 km from landslide location on 9 March showed the range value from 0.5–2.5 mm/hour that is located in the east side of the landslide location with the duration over 1 hour.